Efektifitas Kombinasi Limbah Sayur dan Kotoran Sapi Sebagai Bahan Utama Pembuatan Biogas dalam Digester Anaerob - Yudha Heldy Cahyono; Naniek Ratni JAR (Yayasan Literasi Sains Indonesia, 2023)
Livestock manure which is produced every day can be a problem for the environment if not handled properly. Vegetable waste is generally only allowed to accumulate in the market and immediately disposed of in a landfill without further processing, it can pollute the environment and disturb the aesthetics of the environment. Utilization of organic waste as raw material for renewable energy can be a solution. This study aims to determine the C/N ratio, methane gas production and flames produced from biogas production, as well as knowing the ratio of the ratio of substrate composition and the optimum time to produce the best biogas. This study combined Vegetable Waste (VW) and Cow Manure (CM) with ratio of 90:10, 70:30, 50:50, 30:70, 10:90. Variation of fermentation time was carried out for 5 days, 10 days, 15 days, 20 days and 25 days using a 19 liter volume reactor. The results show that the best ratio of substrate composition in biogas production is VW:CM 70:30 with a C/N ratio of 21.39% and produces 93.78% methane gas and produces a blue flame for 102.35 seconds.